Poverty and basic needs - World Bank. (Washington, D.C., U.S.A. : World Bank, 1980)
"What Government Can Do argues that federal, state, and local governments can and should do a great deal. Benjamin I. Page and James R. Simmons detail what programs have worked and how they can be improved, while introducing the general reader to the fundamentals of social insurance programs such as Social Security and Medicaid, tax structures, minimum wage laws, educational programs, and the concept of "basic needs." Through their discussions of high-profile campaign plans, proposals, successes, and failures, they have written a readable, optimistic, and clear-headed book on government and poverty. And they find that, contrary to popular belief, government policies already do, in fact, help alleviate poverty and economic inequality. Often these policies work far more effectively and efficiently than people realize, and in ways that enhance freedom rather than infringe on it. At the same time, Page and Simmons show how even more could be - and should be - accomplished.
Cover title.
Articles originally appeared in Finance & development magazine.
"September 1980."
Includes bibliographies.
aia 13/02/2019
Loans
Keywords: Basic needs; Developing countries